Palladium-catalyzed coupling reactions on functionalized 2-trifluoromethyl-4-chromenone scaffolds. Synthesis of highly functionalized trifluoromethyl-heterocycles - Izquierdo, Javier (Synthesis (Stuttg), 2019)
The chromenone core is a ubiquitous group in biologically-active natural products and has been extensively used in organic synthesis. Fluorine derived compounds, including those with a trifluoromethyl group (-CF(3)), have shown enhanced biological activities in numerous pharmaceuticals compared with their non-fluorinated analogs. We have found that 2-trifluoromethyl chromenones can be readily functionalized in the 8- and 7-positions, providing chromenones cores of high structural complexity which are excellent precursors for numerous trifluoromethyl-heterocycles.